Policy-based network management solutions for the next generation - Strassner, John C. (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2004)
Policy-Based Network Management (PBNM) systems enable business rules and procedures to be translated into policies that configure and control the network and its services. Those who manage network systems are aware that this approach can benefit both network management as well as the development of applications that use network services; however, the details surrounding these systems has been obscured by marketing hype, numerous acronyms, and theoretical complexities. Policy-Based Network Management: Solutions for the Next Generation cuts through the hype surrounding PBNM and makes it approachable for those who really need to understand what it has to offer. The author, founder of the IETF Policy Framework working group, discusses system requirements, information models, and system components for Policy-Based Management. He also provide practitioners with a resource for developing and/or incorporating PBNM systems. As network systems become larger and more complex, creating policies for them has become a crucial step in the management of network systems, and this book is a welcome addition to this exciting approach. * Presents a completely new approach to PBNM that unites the business, system, and implementation spheres. * As the basis for examples and discussion, uses the DEN-ng information model, an easy-to-understand open standard tied closely to eTOM and NGOSS. * Introduces the Ponder system, then examines Ponder extensions designed to enhance the structure of high-level policies and their application in a PBNM system. * Filled with examples illustrating how policies are most effectively used in a PBNM system and what new directions PBNM is likely to take.
The foundation of policy management -- Policy management fundamentals -- Policy management and the sharing of data -- Policy operation in a PBNM system -- Representing high-level policies -- Motivation for the DEN-ng policy model -- The DEN-ng policy model -- Components of a PBNM system -- Examples of using the policy continuum -- Application of PBNM concepts -- New directions in policy-based management.
Includes bibliographical references and index.
Keywords: Computer networks -- Management; Computer networks -- Security measures; Electronic books